Soil Loss Assessment in Western High Atlas of Morocco: Beni Mohand Watershed Study Case - Latifa Bou-imajjane; Mhamed Alaeddine Belfoul (Applied and Environmental Soil Science)
Soil loss triggered by water erosion constitutes a major issue that causes several environmental and socioeconomic concerns. The Moroccan Western High Atlas is the most vulnerable area in the High Atlas Mountains, due to the existence of different forms of landslides, and evidences of erosion are widely observed. This study aims at estimating and quantifying the amount of soil loss as well as highlighting potential areas to erosion risk, using the Revised Universal Soil Loss Equation (RUSLE) combined with GIS and remote sensing. The RUSLE model provides a possibility of computing erosion susceptibility for each pixel on the basis of the controlling factors which are rainfall aggressivity, topography, vegetation cover, soil erodibility, and support practices. In this study, results show that the erosion rate varies between 0 and 227.67 t/ha/year, with an average annual soil loss of 40.38 t/ha/year, and the Beni Mohand River basin is subject to very high rates of erosion which can be irreversible since it exceeds the tolerable standard rate which is 1 t/ha/year. These findings will provide land use planners baseline for land use and risk management and will provide data within the Moroccan Western High Atlas Mountains.